PECULIAR FEATURES OF EVIDENCE AT THE TERMINATION OF A CRIMINAL CASE (TSUL LEGAL REPORT, 2026)
This article analyzes the importance of proof and its features at the stage of termination of a criminal case based on the norms of criminal and criminal procedure legislation at the implementation stage of judicial reform. The article studies this institution’s scope through the views scientists expressed on proving when closing a criminal case. Based on the views and ideas put forward by scientists, the issue of proof in the termination of a criminal case is analyzed through scientific, theoretical, practical, and legal norms.The article analyzes the grounds for terminating a criminal case through a comparative analysis of the opinions of scientists on the issue of proving when terminating a criminal case. Based on the analysis results, conclusions, proposals, and recommendations aimed at improving the evidence in the termination of a criminal case have been developed.